Effect of taurine on histopathological features of spermatogenesis in seminiferous tubules of mice (Mus musculus) induced by paraquat - Rahadi, Yustisiane Ruth; Tri Wahyu Suprayogi; Rahmi Sugihartuti; Kadek Rachmawati; Hani Plumeriastuti (Universitas Airlangga, 2022)
This study aimed to determine the effect of taurine on the enhancement of the spermatogenetic process in male mice (Mus musculus) induced by paraquat (PQ). Twenty-five male mice (Mus musculus) aged 2-3 months with a bodyweight of around 35 grams were divided randomly into five groups. The K + and the treatment group (P1, P2, and P3) mice were induced using PQ. PQ was given intraperitoneally (IP) twice a week for 21 consecutive days at a dose of 30 mg/kg BW. Two hours after the administration of PQ, P1, P2, and P3 groups were given taurine at a dose of 250, 500, and 1000 mg/kg BW/day for three weeks (Heidari et al., 2019). K- group was given distilled water (IP) only. On day-29, mice were sacrificed for testicles histopathological preparations with hematoxylin-eosin staining. Results showed that the mice exposed to PQ only (the K+ group) had a reduced spermatogenesis score compared to those of the K- group (p <0.05). Taurine treatment on PQ-exposed mice was followed by an increase spermatogenesis score. The optimal curative dose of taurine was 500 mg/kg (P2 group). However, a higher dose (1000 mg/kg BW) of taurine resulted in a decline in the spermatogenesis score than those of at the 500 mg/kg. It could be concluded that treatment with taurine could enhance the spermatogenetic process of male mice (Mus musculus) induced by PQ.